2021
DOI: 10.1007/s10875-021-01136-x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-existing Autoantibodies Neutralizing High Concentrations of Type I Interferons in Almost 10% of COVID-19 Patients Admitted to Intensive Care in Barcelona

Abstract: Background It is important to predict which patients infected by SARS-CoV-2 are at higher risk of life-threatening COVID-19. Several studies suggest that neutralizing auto-antibodies (auto-Abs) against type I interferons (IFNs) are predictive of critical COVID-19 pneumonia. Objectives We aimed to test for auto-Abs to type I IFN and describe the main characteristics of COVID-19 patients admitted to intensive care depending on whether or not these auto-Abs are present. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
57
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 30 publications
4
57
1
Order By: Relevance
“…We observed a very rapid and robust induction of the Type I IFN pathway at 1-2dpi, characterized by elevated pDCs in the airway and blood, IFNA and IFNB transcripts and protein, upregulated ISGs, and increased granzyme B in NK cells. The Type I IFN response in SARS-CoV-2 infection has been intensely studied: in vitro infection of airway epithelial cells have consistently resulted in a muted ISG response 43 , and patients developing severe COVID-19 have been reported to have higher incidence of mutations in IFN response genes, or elevated levels of autoantibodies against IFN-response genes (reviewed in 6,[44][45][46][47][48][49][50][51] ). Our data, in which the IFN response peaked at 2dpi and had largely abated by 10/11dpi, provides well defined kinetics of the ISG response, and similar observations have been reported in other NHP studies 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…We observed a very rapid and robust induction of the Type I IFN pathway at 1-2dpi, characterized by elevated pDCs in the airway and blood, IFNA and IFNB transcripts and protein, upregulated ISGs, and increased granzyme B in NK cells. The Type I IFN response in SARS-CoV-2 infection has been intensely studied: in vitro infection of airway epithelial cells have consistently resulted in a muted ISG response 43 , and patients developing severe COVID-19 have been reported to have higher incidence of mutations in IFN response genes, or elevated levels of autoantibodies against IFN-response genes (reviewed in 6,[44][45][46][47][48][49][50][51] ). Our data, in which the IFN response peaked at 2dpi and had largely abated by 10/11dpi, provides well defined kinetics of the ISG response, and similar observations have been reported in other NHP studies 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…This article is a US Government work. It is not subject to copyright under 17 105 and is also made available for use under a CC0 license.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-existing antibody populations may also contribute to disease severity such as autoantibodies to type I interferons (17). As SARS-CoV-2 mutates, changes to the sensitivity of pre-exisitng neutralizing antibody populations may be effected (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al found enrichment in loss-of-function mutations at loci involved in type I IFN production in patients with life-threatening SARS-CoV-2 infection compared to healthy controls [ 50 ]; such susceptibility mutations are rare, but do contribute to the low interferon levels seen in severe disease. Neutralising autoantibodies to type I IFNs have been identified in ∼10% of patients with severe SARS-CoV-2 infection [ 51 , 53 , 54 ]. The presence of type 1 IFN autoantibodies appear to be a poor prognostic sign [ 53 ] and have been implicated in approximately one fifth of deaths from SARS-CoV-2 [ 55 ].…”
Section: Systemic Immune Responsesmentioning
confidence: 99%